2021
DOI: 10.2298/vsp181116038s
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dental caries and restorative biomaterials on IL-1 β and TNF-α levels in the gingival crevicular fluid

Abstract: Background/Aim.To estimate the concentrations of the proinflammatory cytokines (IL-1β TNF-in the gingival crevicular fluid (GCF) samples from caries affected teeth and intact teeth, and to correlate them with caries extension, tooth position, and different restorative biomaterials. Methods.GCF samples were collected from the 90 periodontally healthy patients demonstrating at least one tooth with proximal caries and one intact tooth, at the baseline, 7 and 30 days post-treatment. The biomarkers profile was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(79 reference statements)
1
1
0
Order By: Relevance
“…Additionally, the lack of any signi cant correlations between the concentrations of IL-1β in the periapical uid of teeth, GCF and serum is quite apparent. Our nding is concordance with some previous systematic review that mentions of reports which arrived at nal conclusion [29], but in con icting opinion, with Stefanović V, et al [30]. This contradiction between these ndings may be due to heterogeneity and limitation of the study designs.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the lack of any signi cant correlations between the concentrations of IL-1β in the periapical uid of teeth, GCF and serum is quite apparent. Our nding is concordance with some previous systematic review that mentions of reports which arrived at nal conclusion [29], but in con icting opinion, with Stefanović V, et al [30]. This contradiction between these ndings may be due to heterogeneity and limitation of the study designs.…”
Section: Discussionsupporting
confidence: 91%
“…To date, IL-1β is the most extensively studied cytokine in relation to the effects or influence that different prosthetic materials may have on the periodontium, including other temporary restorative materials such as dental cements and nanohybrid composites [ 127 ]. In fact, it has been observed that patients with zirconia-based fixed dental prostheses show a decrease in IL-1β levels compared to those with porcelain metal prostheses and temporary prosthetic materials, such as PMMA, where there is a very slow decrease in this cytokine indicating a more inflammatory state [ 28 , 29 , 32 , 40 , 41 ].…”
Section: Oral Biomarkersmentioning
confidence: 99%